2013
DOI: 10.1016/j.nrl.2012.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Impacto económico y en calidad de vida de la epilepsia resistente en España: estudio ESPERA

Abstract: Results suggest that DRE is associated with increased use of healthcare resources and consequently with higher costs, poorer quality of life and higher incidence of major depression compared to seizure-free patients, thus representing a considerable burden to the SNS and society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“… What this study adds to the field This is the first study using perampanel in Asian population for patients with epilepsy, which revealed the 50% responder rate (45.8%) and treatment emergency adverse event (39.5%) similar to the studies of Europe and North American. Uncontrolled seizures reduce patients' quality of life [1] and increase mortality [2] . Although several antiepileptic drugs (AEDs) have been developed in the past 20 years, the proportion of patients that have achieved seizure-free status is suboptimal, and high drug resistance rates persist.…”
mentioning
confidence: 99%
“… What this study adds to the field This is the first study using perampanel in Asian population for patients with epilepsy, which revealed the 50% responder rate (45.8%) and treatment emergency adverse event (39.5%) similar to the studies of Europe and North American. Uncontrolled seizures reduce patients' quality of life [1] and increase mortality [2] . Although several antiepileptic drugs (AEDs) have been developed in the past 20 years, the proportion of patients that have achieved seizure-free status is suboptimal, and high drug resistance rates persist.…”
mentioning
confidence: 99%
“…Emotional distress, social isolation and stigmatization, dependence on family, poor employment opportunities, and personal injury add to the suffering of PWE [38,39]. A number of studies, including data from Spain, have demonstrated the negative impact of DRE in patients' healthrelated quality of life (HRQOL) [40][41][42][43]. Its association with high unemployment rates and occupational incapacity has also been reported [41,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies, including data from Spain, have demonstrated the negative impact of DRE in patients' healthrelated quality of life (HRQOL) [40][41][42][43]. Its association with high unemployment rates and occupational incapacity has also been reported [41,44,45]. More than one-third of patients need a caregiver for day life activities [44] and caregivers' quality of life is also negatively impacted both physically and mentally [46].…”
Section: Discussionmentioning
confidence: 99%
“…• The psychosocial burden of epilepsy. Epilepsy may lead to decreased quality of life, which is associated with occurrence of depression 9 . In a study by Novy et al 10 , high social burden in epilepsy cases explained the association with psychiatric comorbidities.…”
Section: Introductionmentioning
confidence: 99%